2021
DOI: 10.1080/10717544.2021.1923862
|View full text |Cite
|
Sign up to set email alerts
|

Development of a PHBV nanoparticle as a peptide vehicle for NOD1 activation

Abstract: NOD1 is an intracellular receptor that, when activated, induces gene expression of pro-inflammatory factors promoting macrophages and neutrophils recruitment at the infection site. However, iE-DAP, the dipeptide agonist that promotes this receptor's activation, cannot permeate cell membranes. To develop a nanocarrier capable of achieving a high and prolonged activation over time, iE-DAP was encapsulated in nanoparticles (NPs) made of poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV). The physicochemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The research developed by Cabaña-Brunod et al [126] has found that PHBV nanoparticles (NPs) could be effectively used as a delivery system for iE-DAP, a NOD1 (intracellular receptor) agonist. The NPs showed controlled release of iE-DAP in-vitro, and the response of the encapsulated agonist was found to be higher than its free form.…”
Section: Drug Deliverymentioning
confidence: 99%
“…The research developed by Cabaña-Brunod et al [126] has found that PHBV nanoparticles (NPs) could be effectively used as a delivery system for iE-DAP, a NOD1 (intracellular receptor) agonist. The NPs showed controlled release of iE-DAP in-vitro, and the response of the encapsulated agonist was found to be higher than its free form.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Further studies also indicate that intradermal and nasal administration of MDP-encapsulated N-trimethyl chitosan nanoparticles could increase the immunogenicity of antigens [233]. In a separate study, Mauricio et al developed an iE-DAP-loaded biocompatible poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) nanoparticle, and found that the nanoparticle could be taken up by cells effectively [238]. Intriguingly, this nanoparticle enables a sustained and controlled release of cargo.…”
Section: Nod Signalingmentioning
confidence: 99%
“…Carbohydrate polymers have been recognized for their favorable characteristics, including good biocompatibility, inherent nontoxicity, and biodegradability. , Among these polymers, poly­(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) stands out as a biodegradable biopolymer derived from starch through fermentation engineering technology . Notably, PHBV has demonstrated its ability to form polymeric NPs that can encapsulate compounds and regulate their release. Compared to other polymers like poly­(lactic- co -glycolic acid) (PLGA), PHBV exhibits advantages such as biodegradability, nontoxicity, and low production cost . Furthermore, PHBV NPs have exhibited effective control over the release rate of encapsulated drugs, making them a promising candidate for drug delivery systems that respond to the tumor microenvironment …”
Section: Introductionmentioning
confidence: 99%